Early‐onset Dementia with Lewy Bodies - Takao, Masaki (Brain Pathol, 2006)
The clinical and neuropathological characteristics of an atypical form of dementia with Lewy bodies (DLB) are described. The proband experienced difficulties in her school performance at 13 years of age. Neurological examination revealed cognitive dysfunction, dysarthria, parkinsonism and myoclonus. By age 14 years, the symptoms had worsened markedly and the proband died at age 15 years. On neuropathological examination, the brain was severely atrophic. Numerous intracytoplasmic and intraneuritic Lewy bodies, as well as Lewy neurites, were present throughout the cerebral cortex and subcortical nuclei; vacuolar changes were seen in the upper layers of the neocortex and severe neuronal loss and gliosis were evident in the cerebral cortex and substantia nigra. Lewy bodies and Lewy neurites were strongly immunoreactive for α‐synuclein and ubiquitin. Lewy bodies were composed of filamentous and granular material and isolated filaments were decorated by α‐synuclein antibodies. Immunohistochemistry for tau or β‐amyloid yielded negative results. The etiology of this atypical form of DLB is unknown, since there was no family history and since sequencing of the exonic regions of α‐Synuclein, β‐Synuclein, Synphilin‐1, Parkin, Ubiquitin C‐terminal hydrolase L1 and Neurofilament‐M failed to reveal a pathogenic mutation. This study provides further evidence of the clinical and pathological heterogeneity of DLB.